2019
DOI: 10.1111/dme.14145
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype, genotype and glycaemic variability in people with activating mutations in the ABCC8 gene: response to appropriate therapy

Abstract: Aims To examine the phenotypic features of people identified with ABCC8-maturity-onset diabetes of the young (MODY) who were included in the adult 'Mater MODY' cohort and to establish their response to sulfonylurea therapy. Methods Ten participants with activating ABCC8 mutations were phenotyped in detail. A 2-hour oral glucose tolerance test was performed to establish glycaemic tolerance, with glucose, insulin and C-peptide measurements taken at baseline and 30-min intervals. Insulin was discontinued and sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…This figure is available as part of a downloadable slideset [37]. For example, sulfonylureas are effective as a treatment for MODY caused by mutations in HNF1A or HNF4A and, at low dose, ABCC8 genes [38]. GCK mutations cause stable fasting hyperglycaemia with a higher set point of glucose that does not require treatment except during pregnancy [39].…”
Section: Heterogeneity Of Diabetes Within Types and Clinical Consequementioning
confidence: 99%
“…This figure is available as part of a downloadable slideset [37]. For example, sulfonylureas are effective as a treatment for MODY caused by mutations in HNF1A or HNF4A and, at low dose, ABCC8 genes [38]. GCK mutations cause stable fasting hyperglycaemia with a higher set point of glucose that does not require treatment except during pregnancy [39].…”
Section: Heterogeneity Of Diabetes Within Types and Clinical Consequementioning
confidence: 99%
“…The phenotype of kidney disease among the patients with the variants of ABCC8 was also previously described. [42][43][44] A recent study has shown that homozygous ABCC8 p. E1506K +/+ variant knock-in mice presented with hyperinsulinemia in early life, followed by diabetes and early DKD in late life. The histologic differences in the kidneys of ABCC8 E1506K +/+ mice were well established at 32 weeks compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Rafiq et al [85] suggested that all carriers of ABCC8 mutations could be switched to sulphonylureas, also in adulthood. More recently, Reilly et al [86] described ten patients with a mean age of 33.8 years at diagnosis treated with insulin or diet or metformin at recruitment. The HbA1c value was 6.9% after the molecular diagnosis and 6.2% after the switch to the anti-diabetic medication gliclazide (mean daily dose 36.87 ± 32.2 mg).…”
Section: Abcc8-mody or Mody12mentioning
confidence: 99%